1988
DOI: 10.1210/mend-2-10-952
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Ribonucleic Acid from the Unactivated Rat Liver Glucocorticoid Receptor

Abstract: We have reported that the 7-8S form of the rat liver glucocorticoid receptor is associated with RNA. Whether the unactivated 9-10S form of the glucorticoid receptor is also associated with RNA is less clear. Here we provide evidence that the unactivated 9-10S receptor is indeed associated with RNA. Unactivated 9-10S receptor was partially purified by diethylaminoethyl (DEAE)-cellulose chromatography in the presence of molybdate, an activation inhibitor. This preparation was then bound to BuGR-2, a mouse monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, there are also reports that a highly purified 9-10 S receptor preparation from rat liver contains RNA . Furthermore, we have shown that, when 9-10 S receptor is isolated with monoclonal antibody to the receptor, distinct species of RNA are found in the receptor preparation (Unger et al, 1987).…”
Section: Introductionmentioning
confidence: 94%
“…However, there are also reports that a highly purified 9-10 S receptor preparation from rat liver contains RNA . Furthermore, we have shown that, when 9-10 S receptor is isolated with monoclonal antibody to the receptor, distinct species of RNA are found in the receptor preparation (Unger et al, 1987).…”
Section: Introductionmentioning
confidence: 94%